Implementasi Teknik Penilaian Kognitif Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Covid-19 - Heikal Syah Alam; Andi Prastowo (JIE (Journal of Islamic Education), 2022)
The direction of this research aims to represent a model of implementing cognitive assessment techniques for Islamic religious education during the COVID-19 pandemic. This research includes qualitative research with the type of field research. The research data were taken from primary data and secondary data relevant to the research. Sources of data were obtained from interviews with teachers of Islamic religious education subjects via WhatApps while secondary data were obtained from documents and teacher learning journals. The analysis technique used is to present the results of the study, then reduce the data from the research results and finally verify the data. The results of the research in general can be conveyed as follows: (1) Cognitive assessment in Islamic religious education learning has the function of measuring the scale of students' ability to understand a material on an ongoing basis (2) This cognitive technique includes: multiple choice, short entry, matchmaking, description, oral tests, portfolios, projects and products (3) models of cognitive techniques during the pandemic in Islamic education learning using supporting tools that are easily accessible to each student and teacher. In the future, when the atmosphere returns to normal, it is hoped that educational institutions will be able to create the latest innovations in developing cognitive assessment techniques.